Dietary copper absorption and excretion in three semi-terrestrial grapsoid crabs with different levels of terrestrial adaptation - Sa, M. G.; Valenti, Wagner Cotroni [UNESP]; Zanotto, F. P. (Elsevier B.V., 2008)
Three species of phylogenetically related semi-terrestrial crabs (Superfamily Grapsoidea - Sesarma rectum, Goniopsis cruentata and Neohelice granulata (formerly: Chasmagnathus granulatus) with different degrees of terrestriality were studied to quantify the accumulation of copper (Cu) in hemolymph, gills, hepatopancreas and antennal gland, and its excretion through the faeces. These crabs were fed for 15 days practical diets containing 0 (A), 0.5 (B), 1.0 (C), and 1.5% (D) of added CuCl2 (corresponding to 0, 0.2, 0.5 and 0.7% of Cu2+, respectively). The amount of food ingested was directly proportional to the degree of terrestriality: S. rectum, the most terrestrial species, ate around 2-3 times more than the other crabs, whereas G. cruentata ate 1.5-2 times more than N. granulata, the least terrestrial. The amount of Cu excreted in the feces was proportional to Cu ingestion, and was 76.8% and 64.2% higher for Sesarma fed diet D compared to G. cruentata and N. granulata, respectively. Sesarma also displayed higher Cu concentration in the haemolymph, gills and antennal glands, but not in the hepatopancreas. A detoxifying mechanism followed by elimination was probably present at this last organ, preventing Cu accumulation. More terrestrial crabs, such as Sesarma, may accumulate more Cu in hemolymph and tissues, showing a correlation between metal accumulation and increased terrestriality. In this aspect, contaminated feed sources with Cu may have more impact in conservation of terrestrial crabs. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: bioaccumulation; brachyura; nutrition; terrestrial crabs